Digital Marketing Public Relations Lorong Temu Coffee and Eatery di masa Pandemik Covid-19 - Regista Nurul Adriati; Tresna Wititan (Bandung Conference Series: Public Relations, 2022)
Abstract. By 2021, the entire world has been hit by the COVID-19 pandemic, including Cianjur Regency. As a result, all community activities are diverted into the virtual world. Facing such conditions, business actors must be able to adapt to these conditions and maintain their brand awareness. Lorong Temu, a cafe and restaurant located in the heart of Cianjur District, has adapted to those condition by maximizing the work of Digital Marketing Public Relations (DMPR) ahead of the pandemic. This study aims to explain how the process of planning and implementing DMPR work in Lorong Temu, and optimizing Instagram social media in the performance of the DMPR. This study uses a qualitative descriptive method based on data collection in the form of literature review and interviews. In this study, the authors interviewed Lorong Temu CEO and CMO, Nazer Vikran and Alvi Khoirunnisa and DMPR practitioners who worked with Lorong Temu, namely representatives from Pop Creative Labs, Alya Novinda and Isni Suci. In addition, the author also analyzes the optimized social media content, namely the @lorongtemu Instagram account. The theory used in this study is the Excellence Theory by Gruning & Hunt (1984). Based on the results of this research conducted by the author, the DMPR work planning process in Lorong Temu was carried out after going through an intense dialogue between Lorong Temu and Pop Creative Labs. Based on the dialogue, Lorong Temu and Pop Creative prepared various DMPR agendas. Starting from scheduling Instagram content, publishing various creative content, to organizing the Lorong Temu Birthday event which held on September 10, 2021. Through optimizing the event's campaign through Instagram, Lorong Temu and Pop Creative labs have been proven to be able to carry out DMPR activities effectively and efficiently. Abstrak. Menjelang tahun 2021, seluruh dunia telah dilanda pandemi covid-19 tak terkecuali Kabupaten Cianjur. Akibatnya, segala kegiatan masyarakat dialihkan ke dalam dunia virtual. Menghadapi kondisi demikian, pelaku usaha harus bisa beradaptasi dengan kondisi tersebut dan mempertahankan agar brand awareness di masyarakat turut meningkat. Lorong Temu, sebuah kafe dan resto yang berada di jantung Kecamatan Cianjur melakukan adaptasi dengan memaksimalkan kerja Digital Marketing Public Relations (DMPR) menjelang pandemi. Penelitian ini bertujuan untuk menjelaskan bagaimana proses perencanaan dan penerapan kerja DMPR di Lorong Temu, dan optimalisasi media sosial Instagram dalam kinerja DMPR tersebut. Teori yang digunakan dalam penelitian ini yaitu Excellence Theory oleh Gruning & Hunt (1984). Penelitian ini menggunakan metode deskriptif kualitatif yang berdasarkan pada pengumpulan data berupa sudi pustaka dan wawancara. Dalam penelitian ini, penulis mewawancarai CEO dan CMO Lorong Temu, Nazer Vikran dan Alvi Khoirunnisa serta praktisi DMPR yang bekerja sama dengan Lorong Temu yakni perwakilan dari Pop Creative Labs, Alya Novinda dan Isni Suci. Selain itu, penulis juga melakukan analisa terhadap konten media sosial yang dioptimalkan yakni akun Instagram @lorongtemu. Berdasarkan hasil penelitian yang dilakukan oleh penulis, proses perencanaan kerja DMPR di Lorong Temu dilakukan setelah melalui dialog yang intens antara pihak Lorong Temu dan Pop Creative Labs. Berdasarkan dialog tersebut, pihak Lorong Temu dan Pop Creative menyusun berbagai agenda DMPR. Mulai dari penyusunan jadwal konten Instagram, publikasi berbagai konetn kreatif, hingga penyelenggaraan event Hari Ulang Tahun (HUT) Lorong Temu yang dilaksanakan pada 10 September 2021. Lewat optimalisasi kampanye event tersebut melalui Instagram, Lorong Temu dan Pop Creaive labs telah terbukti mampu menjalankan kegiatan DMPR secara efektif dan efisien. Kata Kunci : Campaign, Digital Marketing Public Relations, Media Sosial